Isolation of Endotoxin Eliminating Lactic Acid Bacteria and a Property of Endotoxin Eliminating Protein. Issue 6 (20th April 2016) - Kondo, Ayaka; Asami, Kyoko; Suda, Yoshihito; Shimoyamada, Makoto; Kanauchi, Makoto
Abstract: Recently, many scholars have reported lactic acid bacteria (LAB) functions, such as anticancer activity and anti‐inflammatory activity for intestines. To decrease inflammatory substances such as endotoxins, LAB consumed safely with meals were isolated from food and food ingredients. First, LAB were isolated as 168 strains of bacillus LAB (49 strain) and coccus LAB (119 strains) from food ingredients and fermented foods such as rice, rice bran, malt, grains, miso soy paste, and some pickles. Their LAB (168 strains) were cultivated in medium containing endotoxin from Escherichia coli O18 LPS at 15 and 30 °C for 64 h to identify endotoxin‐eliminating LAB. Consequently, the AK‐23 strain was screened as an endotoxin‐eliminating LAB strain. The strain decreased endotoxin in YP medium without sugar at 30 °C for 64 h until 9% of endotoxin. The strain was identified as Pediococcus pentosaceus according to morphological characteristics such as its cell shape, physiological characteristics related to its fermentation type, assimilation of sugars, pH tolerance, optimum growth temperature, and molecular biological characteristics as its homology to 16S rRNA. To investigate the location of the endotoxin‐eliminating substance, 4 fractions were separated from AK‐23 cells as extracellular, cell wall digestion, cytoplasm, and cell membrane fractions. The endotoxin‐decreasing substance, located on a cell wall, was identified as a 217 kDa protein.